On the existence of multiple nontrivial solutions for resonant neumann problems - Papageorgiou, Nikolaos
We consider a semilinear second order elliptic problem with Neumann boundary conditions and a nonsmooth potential (hemivariational inequality). Using nonsmooth critical point theory, we establish the existence of at least two nontrivial smooth solutions, when double resonance occurs at the origin between any two distinct successive eigenvalues.